Foreign Direct Investment and Technology Transfers to Local Suppliers: Identifying the effects of type of ownership and the technology gap - Jacob A. Jordaan (European Regional Science Association (ERSA), 2012)
In this paper, I present novel empirical evidence in support of the idea that FDI firms can act as an important driver of regional growth, by acting as a source of new knowledge and technologies to local suppliers in a host economy. For the analysis, I use unique firm level data that I obtained from applying several purpose built surveys among FDI and domestic producer firms as well as local suppliers in the regional economy of Nuevo Leon, Mexico. With this data, I assess the scale and nature of technology transfers between FDI firms and local suppliers and I identify statistically factors that influence the spillover impact that arises from these transfers. The main findings are three]fold. Firsts, I find clear and robust evidence that FDI firms are significantly more involved than domestic producer firms in various knowledge transfer activities, activities with a direct positive impact on production processes of the local suppliers. As a result, suppliers of FDI firms are more likely to experience large positive technological improvements. Second, the analysis shows that a large technology gap between FDI and local suppliers fosters rather than hinders this positive impact among local suppliers of material inputs. This effect persists even when I control for both the level and nature of support that FDI firms provide, suggesting that in particular local suppliers that have a large potential to improve can benefit from their business dealings with FDI firms. Third, I also find that several indicators of the level of absorptive capacity of local suppliers are positively associated with the technology impact that FDI firms create, indicating that there is scope for local policymaking to enhance the positive impact that foreign]owned firms generate in their local host economy.
Keywords: C21; F23; O18; O33; 330; FDI; Local Suppliers; Regional Growth; Technology Transfers; Technology Gap; Absorptive Capacity